2020
DOI: 10.1080/08952841.2020.1727711
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting knowledge about the adult guardianship and civil trust systems: evidence from Japan

Abstract: This study examines the socioeconomic factors influencing public awareness of the adult guardianship and civil trust systems in Japan. The results of this study show that financial literacy is the most influential factor affecting knowledge of the adult guardianship and civil trust systems. Gender, age, living alone, income, and assets are also found to be related to knowledge about these systems, but they are not consistent. We argue that policy makers should emphasize financial literacy and conduct targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…There are two main variables of interest in our study: financial literacy and financial education. We measured financial literacy using Lusardi and Mitchell’s [ 63 ] methodology, which is simple and widely adopted in the existing literature (e.g., [ 48 , 53 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]). Moreover, Nicolini and Haupt [ 72 ] found that the Lusardi–Mitchell measurement of financial literacy performs well unless financial literacy is used to explain financial behavior.…”
Section: Methodsmentioning
confidence: 99%
“…There are two main variables of interest in our study: financial literacy and financial education. We measured financial literacy using Lusardi and Mitchell’s [ 63 ] methodology, which is simple and widely adopted in the existing literature (e.g., [ 48 , 53 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]). Moreover, Nicolini and Haupt [ 72 ] found that the Lusardi–Mitchell measurement of financial literacy performs well unless financial literacy is used to explain financial behavior.…”
Section: Methodsmentioning
confidence: 99%
“…There are two main variables of interest in our study: financial literacy and financial education. To measure financial literacy, we followed Lusardi and Mitchell’s ( 2008 ) methodology, which is simple and widely adopted in existing literature (e.g., Fornero and Monticone 2011 ; Lusardi and Mitchell 2011 , 2014 ; Kadoya and Khan 2019 ; Kadoya et al 2018 , 2020 ; Klapper and Panos 2011 ; Sekita 2011 ), and used the following three questions. Suppose you had ¥10,000 in a savings account and the interest rate is 2% per year and you never withdraw money or receive interest payments.…”
Section: Methodsmentioning
confidence: 99%
“…These questions measure a respondent's knowledge of compound interest, inflation, and risk diversification. Studies such as [22][23][24]34,[48][49][50][51][52][53][54][55] adopted these three questions, which are as follows:…”
Section: Variablesmentioning
confidence: 99%